2020
DOI: 10.1111/evo.13893
|View full text |Cite
|
Sign up to set email alerts
|

Signal evolution and morphological complexity in hummingbirds (Aves:Trochilidae)

Abstract: Understanding how animal signals are produced is critical for understanding their evolution because complexity and modularity in the underlying morphology can affect evolutionary patterns. Hummingbird feathers show some of the brightest and most iridescent colors in nature. These are produced by optically complex stacks of hollow, platelet‐shaped organelles called melanosomes. Neither how these morphologies produce colors nor their evolution has been systematically studied. We first used nanoscale morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 60 publications
(122 reference statements)
1
52
0
Order By: Relevance
“…For instance, iridescence (i.e., the change in color with incidence and/or observation angle and feather orientation) is considered a structural phenomenon. In bird feathers, iridescence is most frequently the result of constructive interference of light with a regular layered or crystal‐like arrangement of melanin granules (Eliason et al, 2020; Prum, 2006). The broadband absorption of light by melanin is also important for the elaboration of the iridescent color effect (Shawkey & D'Alba, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, iridescence (i.e., the change in color with incidence and/or observation angle and feather orientation) is considered a structural phenomenon. In bird feathers, iridescence is most frequently the result of constructive interference of light with a regular layered or crystal‐like arrangement of melanin granules (Eliason et al, 2020; Prum, 2006). The broadband absorption of light by melanin is also important for the elaboration of the iridescent color effect (Shawkey & D'Alba, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the evolution of plumage coloration is increasingly focused on understanding how the different feather elements are combined and genetically regulated (Eliason et al, 2020; Fan et al, 2019; Funk & Taylor, 2019). Small adjustments in the regulatory processes leading to pigment deposition in growing feathers result in conspicuous plumage color differences between populations or species (Campagna et al, 2017; Lopes et al, 2016; Toews et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Gruson et al, 2019 found color production to be similar among patches with different melanosome types in hummingbirds. We speculate that high variability in melanosome type in hummingbirds and birds-of-paradise is not related to general optical benefits of specific melanosome types or modifications, but rather to general high rates of color change in these groups (Eliason et al, 2020; Parra, 2010). Our optical modeling results (Figure 6B-E) show that there are multiple ways to reach the same areas of color space—using different melanosome types.…”
Section: Discussionmentioning
confidence: 92%
“…[18][19][20][21] The extreme iridescence of hummingbird feathers is created by stacks of air-lled melanosome platelets in the barbules. 1,[22][23][24][25] Peacock feather barbules contain a rectangular lattice of solid melanosomes and air channels, which is a unique arrangement compared to other iridescent birds. The anatomy of peacock feathers has been studied in extensive detail by Durrer.…”
Section: Introductionmentioning
confidence: 99%